2021
DOI: 10.3389/fcell.2020.571676
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Alcohol Cedrol Chemosensitizes Human Cancer Cells and Suppresses Cell Proliferation by Destabilizing Plasma Membrane Lipid Rafts

Abstract: Chemosensitization of cancer cells with small molecules may improve the therapeutic index of antitumoral agents by making tumor cells sensitive to the drug regimen and thus overcome the treatment resistance and side effects of single therapy. Cell membrane lipid rafts are known to transduce various signaling events in cell proliferation. Sensitizing cancer cells may cause modulation of membrane lipid rafts which may potentially be used in improving anticancer drug response. Cedrol, a natural sesquiterpene alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…It also exerts inhibitory effects in human lung cancer A549 cells (IC 50 values were 31.88, 14.53, and 5.04 µM at 24, 48, and 72 h) and mediates apoptosis and autophagy through the regulation the PI3K/Akt signaling pathway, generation of reactive oxygen species, and loss of mitochondrial transmembrane potential [29]. In addition, cedrol activates intrinsic apoptosis, suppresses the AKT/ERK/mTOR and NF-κB signaling pathways, and chemosensitizes cancer cells through lipid raft destabilization in human leukemia K562 and colon cancer HT-29 cells, with an IC50 of 179.52 and 185.50 µM at 48 h, respectively [32]. More recently, cedrol was reported to suppress the growth of glioblastoma and triggered apoptosis by the induction of DNA damage and targeting the androgen receptor (IC 50 values of glioblastoma cells were 77.17-141.88 µM at 48 h) [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also exerts inhibitory effects in human lung cancer A549 cells (IC 50 values were 31.88, 14.53, and 5.04 µM at 24, 48, and 72 h) and mediates apoptosis and autophagy through the regulation the PI3K/Akt signaling pathway, generation of reactive oxygen species, and loss of mitochondrial transmembrane potential [29]. In addition, cedrol activates intrinsic apoptosis, suppresses the AKT/ERK/mTOR and NF-κB signaling pathways, and chemosensitizes cancer cells through lipid raft destabilization in human leukemia K562 and colon cancer HT-29 cells, with an IC50 of 179.52 and 185.50 µM at 48 h, respectively [32]. More recently, cedrol was reported to suppress the growth of glioblastoma and triggered apoptosis by the induction of DNA damage and targeting the androgen receptor (IC 50 values of glioblastoma cells were 77.17-141.88 µM at 48 h) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the combination of cedrol and 5-FU had synergistic effects, which enhanced the reduction in the proliferation of HT-29 cells. Cedrol combined with the clinical drug temozolomide also exhibits synergistic suppression in glioblastoma by downregulation of AKT/mTOR signaling and chemosensitizes human leukemia K562 and CRC HT-29 cells by destabilizing plasma membrane lipid rafts [30][31][32]. Therefore, the combination of cedrol and 5-FU may be a promising strategy for overcoming the limitations of 5-FU in CRC treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reprogramming of lipid metabolism that leads to the imbalance of ceramides and S1P also contribute to the dysregulation of lipid raft dynamics. A recent study demonstrated the efficacy of Cedrol in inhibiting HT29 CRC cell growth by destabilising lipid rafts through the redistribution of cholesterol from the plasma membrane, blocking Akt/mTOR signalling and inducing mitochondrial intrinsic apoptosis, thereby resisting cell death [ 171 ]. In a study of colonic cancer stem cell (CSC), impairment of cholesterol biosynthesis by deletion of key synthetic enzymes HMGCR or FDPS lead to reduced spheroid tumorigenic potential via activated TGF-β signalling [ 78 ], a key growth evasion pathway in cancer [ 7 ].…”
Section: Lipid-associated Hallmarks Of Crcmentioning
confidence: 99%
“…Cedrol has been reported to exhibit a number of biological activities, including anticancer [92][93][94] and anti-inflammatory. For example, cedrol was shown to have analgesic and anti-inflammatory effects in complete Freund's adjuvant (CFA)-induced arthritis in rats [95] and in mice with collagen-induced arthritis (CIA) [96].…”
Section: Identification Of Potential Protein Targets For Cedrolmentioning
confidence: 99%